Mýty - omyly - nepravdy O "chibách" ve vzdělávání a pedagogice - Dammer, Karl-Heinz (Reflexe, 2020)
Title in English: Mythos - misunderstandings - fallacies: On failures in education and pedagogy. The book is the translation from Mythen - Irrtümer - Unwahrheiten: Essays über das "Valsche" in der Pädagogik edited by H. U. Grunder (Bad Heilbrunn: Verlag Julius Klinkhardt, 2017). It includes seven essays written by authors from Germany and Switzerland. They strive for profound understanding of issues as upbringing, education, school, teachers, students, teaching and learning.